Establishing patterns in eliminating coal fire sites with nitrogen-air mixtures - Tsapko, Yuriy; Tkachenko, Tetiana; Kasianova, Oksana; Tsapko, Аleksii; Likhnyovskyi, Ruslan; Bereznutska, Yuliia; Prisyazhnuk, Vitally; Slutska, Oksana; Bedratiuk, Olga (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study was the value of nitrogen concentration at which the combustion process of anthracite is effectively inhibited. Therefore, the problem of eliminating the sites of self-ignition of coal relates to ventilating the pile with nitrogen, but it is necessary to take into account the required concentration of inert gas. It has been proven that on the basis of experimental studies of the process of inhibition of combustion when washing an anthracite batch with gaseous nitrogen, a sample of heated coal in a normal air atmosphere continues to burn with greater intensity. An increase in temperature by an average of 20 °C was recorded for 40–45 s. Adding nitrogen to the air in an amount of 12.85 % reduces the combustion temperature of anthracite by 2 %, but the cooling time of combustion below the ignition temperature exceeds 120 s. For a nitrogen-air mixture with a nitrogen concentration of 23.81 %, a decrease in the combustion temperature of the sample below its ignition for 120 s was recorded. Further increase in the amount of nitrogen in the nitrogen-air mixture to 28.57 % more effectively cools the combustion of anthracite below the ignition temperature for 70 s. The results showed that with an increase in the concentration of pure nitrogen in the nitrogen-air mixture, the requirements for the purity of nitrogen as a fire extinguishing agent increase. Therefore, it is necessary to introduce it into the i-th nitrogen-oxygen composition in such a concentration that the nitrogen content in the formed mixtures with air in both cases is the same. This is due to the fact that the purity of the nitrogen-oxygen mixture and its fire extinguishing concentration reflect the conditions under which there is the use of nitrogen-oxygen mixtures of a certain composition for fire extinguishing. The practical significance is that the results of determining the fire extinguishing concentration of nitrogen make it possible to establish the operating conditions of coal storage facilities during the elimination of fire sites